INTEGRATION ANALYSIS OF THERMAL AND DAYLIGHT PERFORMANCE THROUGH THE BUILDING ENVELOPE - Alifiano Rezka Adi; Muhammad Afiq; Didung Putra Pamungkas (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2022)
Several strategies in reducing external heat gain sometimes have an impact on limited access to daylight in buildings. Therefore, an integrated study is needed between thermal and daylight performance of the building. This research focuses on building modeling and simulation on one of the buildings at UIN Walisongo Semarang to see these two parameters based on Standard Nasional Indonesia. The thermal performance through OTTV value is simulated using EnergyPlus, while the building daylight is simulated using Dialux. The existing condition showed that the thermal performance is not fully integrated with the building natural lighting. Further simulation is needed through the building envelope engineering. The results showed that the entire room has met the standard of natural lighting while maintaining the OTTV value according to the standard. This condition is the optimal point which represents the integration between thermal and daylight performance of the building.